May the force be with you: Exit barriers, governance shocks, and profitability sclerosis in banking - Michael Koetter; Carola Müller; Felix Noth; Benedikt Fritz (Deutsche Bundesbank, 2018)
We test whether limited market discipline imposes exit barriers and poor profitability in banking. We exploit an exogenous shock to the governance of governmen-owned banks: the unification of counties. County mergers lead to enforced governmen-owned bank mergers. We compare forced to voluntary bank exits and show that the former cause better bank profitability and efficiency at the expense of riskier financial profiles. Regarding real effects, firms exposed to forced bank mergers borrow more at lower cost, increase investment, and exhibit higher employment. Thus, reduced exit frictions in banking seem to unleash the economic potential of both banks and firms.
Keywords: G21; G29; O16; 330; political frictions; governance; excess capacity; banking; market exit